2015
DOI: 10.1002/jmv.24177
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of T-cell subsets and their relationship with oral and systemic opportunistic infections in HIV/AIDS patients during the first year of HAART in Guangxi, China

Abstract: To analyze the dynamic changes in Th1, Th2, Tc1, and Tc2 of HIV/AIDS patients during the first year of highly active antiretroviral therapy (HAART) and to explore their relationship with oral and systemic opportunistic infections, a cohort study was carried out among HIV/AIDS patients in Guangxi, China. Ninety HIV/AIDS patients and 30 healthy controls (HC) were included. The enrolled HIV/AIDS patients were examined at baseline and after 3, 6, and 12 months of HAART. On each visit, oral and systemic opportunist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(46 reference statements)
2
3
0
Order By: Relevance
“…Overall the high burden of candidiasis observed here cannot be attributed solely to defects in the induction of -defensins. A role for systemic defects in T-cell immunity has been argued as there are clear correlations with a Th1 environment (Zhang et al, 2015). This would be consistent with the parallel between susceptibility to Candida and tuberculosis, and by the resolution of most cases of candidiasis on ART.…”
Section: Discussionsupporting
confidence: 54%
“…Overall the high burden of candidiasis observed here cannot be attributed solely to defects in the induction of -defensins. A role for systemic defects in T-cell immunity has been argued as there are clear correlations with a Th1 environment (Zhang et al, 2015). This would be consistent with the parallel between susceptibility to Candida and tuberculosis, and by the resolution of most cases of candidiasis on ART.…”
Section: Discussionsupporting
confidence: 54%
“…The study demonstrated that increasing VL was independently associated with increased risk, it was consistent with other study [ 44 ]. Furthermore, the study corroborates previous conclusions that HIV VL shows an inverse correlation with CD4 + T cell counts [ 45 ]. HIV infection invades the lymphocytes of the host, leading to compromised immune function and progressive depletion and functional limitations of CD4 + T cells.…”
Section: Discussionsupporting
confidence: 90%
“…Opportunistic fungal infections have rapidly emerged as a major driver for mortality in immunocompromised individuals (Brown et al., ). Oral candidiasis is the most common opportunistic fungal infection in HIV‐infected subjects (de Repentigny, Lewandowski, & Jolicoeur, ), especially in patients with CD4 + T cell counts below 200/mm 3 or a high viral load (>3,000 copies/ml) (Jiang et al., ; Tappuni & Fleming, ; Zhang et al., ). In our study, the HIV/AIDS patients were ready to begin ART with low CD4 + T cell counts, which could be the explanation for high prevalence of OC.…”
Section: Discussionmentioning
confidence: 99%
“…Even though C. albicans is a common component of the oral ecology found in up to 75% of humans (Ghannoum et al, 2010), oral Candida colonization might be associated with low CD4 + T cell counts (Mushi et al, 2017), the failure of ART therapy, systemic opportunistic infections, and malignancies in immunocompromised patients (Delgado et al, 2009;Zhang et al, 2015). In our study, the Candida isolation rates ranged from 63% to 81%, which was similar to those ranging from 56.6% to 82% in previous studies when oral rinse technique was used as the methodology for identifying carrier status (Barchiesi et al, 2002;Campisi, Pizzo, Milici, Mancuso, & Margiotta, 2002;Gottfredsson et al, 1999;Lourenco et al, 2017;Owotade, Patel, Ralephenya, & Vergotine, 2013;Patel et al, 2012;Thanyasrisung et al, 2014).…”
Section: Discussionmentioning
confidence: 99%